Antipyretic Activity Test of 70% Ethanol Extract of Red Andong Leaves (Cordyline fruticosa (L) A. Chev) in Male Wistar Rats (Rattus norvegicus) - Elisabeth Oriana Jawa La; Cut Asyifa Baezura Mangkurat Salma; Ni Ketut Esati; Repining Tiyas Sawiji (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Introduction: Fever is a common health problem that can cause discomfort and may lead to serious complications. One alternative treatment for fever is the use of herbal plants that have been proven to possess antipyretic effects, such as red to plant leaves (Cordyline fruticosa (L.) A. Chev). Objective: To evaluate the secondary metabolite content and assess the antipyretic activity of 70% ethanol extract of red ti plant leaves in male Wistar rats induced with fever using 5% peptone. Methodology: This research used a completely randomized design (CRD) with five treatment groups: a negative control group (1% Na-CMC), a positive control group (paracetamol at a dose of 500 mg/kgBW), and three test groups receiving 70% ethanol extract of red ti plant leaves at doses of 1,200 mg/kgBW, 1,800 mg/kgBW, and 2,400 mg/kgBW. Antipyretic activity was assessed by measuring the reduction in body temperature of the test animals, expressed as a percentage of antipyretic power, and statistically analyzed to evaluate the antipyretic effect of the extract. Results: The study showed that the 70% ethanol extract of red to plant leaves tested positive for flavonoids, tannins, and saponins, which are potential antipyretic compounds. Additionally, the extract demonstrated significant antipyretic activity, as indicated by a notable reduction in the body temperature of the test animals. All three doses of the extract resulted in a temperature decrease, with the 2,400 mg/kgBW dose showing the most optimal antipyretic effect, approaching the effectiveness of paracetamol as the positive control. Conclusion: The 70% ethanol extract of red ti plant leaves has been proven to exhibit antipyretic activity, with the 2,400 mg/kgBW dose demonstrating an effect comparable to paracetamol. The extract also contains secondary metabolites such as flavonoids, tannins, phenol, terpenoids and saponins.